A NEW SPECIMEN OF TOXODONTIDAE (NOTOUNGULATA) FROM THE URUMACO FORMATION (UPPER MIOCENE) OF VENEZUELA - Bond M.; Madden R.H.; Carlini A.A. (My University, 2006)
A new specimen of Toxodontidae, consisting of a partial mandibular ramus with three molars, is described from the Middle Member of the Urumaco Formation and compared with type and referred material from all four taxa previously reported from Venezuela and with several better known taxa of advanced Toxodontidae. Incomplete preservation and postmortem distortion make an assessment of its morphology difficult. Despite these shortcomings, the new material does not appear to represent any of the Venezuelan taxa previously described. The specimen shows a unique combination of characters including a pattern of lingual enamel folds, weakly developed meta-entoconid and well-developed ento-hypoconid fold (m1 and m2, not in m3), subrounded and lingually expanded trigonid, transversely broad hypoconid and open labial enamel fold. In this combination of features, the new specimen most closely resembles the types of Trigodonops lopesi and Mixotoxodon larensis.
Keywords: URUMACO FORMATION; FOSSIL MAMMAL; NEOGENE; SOUTH AMERICA; Cenozoic::Neogene; Кайнозой::Неоген